“The Place of Dance in Human Life”: Perspectives on the Fieldwork and Dance Notation of Gertrude P. Kurath - Caldwell, Mary (Ethnologies, 2008)
AbstractThis article provides a brief biographical sketch of Gertrude P. Kurath and introduces her as a central figure in twentieth century dance scholarship. Her role in the emergence of the field of dance studies in the academia is examined and her promotion of the connection between dance studies and anthropology and ethnomusicology is stressed. This article examines in detail two specific features of her scholarship: her forward-looking fieldwork and her innovation and use of movement notation. Both her fieldwork and her use of notation are contextualized within her extensive research on Native American dance.